Pengaruh Motivasi Dan Pengalaman Kerja Terhadap Kinerja Karyawan Di UNP Hotel & Convention - Muhammad Aldri; Yuliana Yuliana (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by several problems, namely, the existence of employees who work not in accordance with hotel standards and quality, often miscommunicate when over handling to the next shift, no training on standard operating procedures (SOP) for employees. The type of research used in this study is quantitative with a causal associative approach. The results of this study indicate that employee work motivation is in the good category, namely 80%. Work experience is in the good category, namely 57.1%, but there are still 11.4% who are classified as sufficient and poor categories. And employee performance is included in the good category, namely 42.9%, but there are still 45.7% who are classified as sufficient and poor categories. The effect of work motivation (X1) and work experience (X2) on employee performance (Y) with an Adjusted R Square value of 0.244 with a sig value. 0.004 < 0.05. This means that 24.4% of employee performance is influenced by work motivation and work experience while 75.6% is influenced by other factors.